MAGISTER OFFICIORUM AND THE «STATE SECRET POLICE» IN THE LATE ROMAN EMPIRE - S. A. Sakharov (Гуманитарные и юридические исследования)
With the reference to «Theodosian Code» and other sources the article studies the powers of the magister officiorum as the head of the late Roman secret service, which in fact carried out functions of the state secret police. According to the late Roman Imperial legislation the Master was directly responsible for the formation of these departments, maintaining the register of the service and the current management. The ofice under the Master consisted of special government agents referred to in the «Theodosian Code» as agentes in rebus. The agents carried out state control and supervision in late Roman provinces, thereby ensuring the safety and order in the Empire.